A new subclass of copper(i) hybrid emitters showing TADF with near-unity quantum yields and a strong solvatochromic effect. Issue 20 (17th February 2023) - Baranov, Andrey Yu.; Rakhmanova, Mariana I.; Hei, Xiuze; Samsonenko, Denis G.; Stass, Dmitri V.; Bagryanskaya, Irina Yu.; Ryzhikov, Maxim R.; Fedin, Vladimir P.; Li, Jing; Artem'ev, Alexander V.
Abstract : We present a unique new subclass of Cu(i ) hybrid complexes, showing TADF with near-unity quantum yields as well as unprecedented solvatochromic emission and strong X-ray radioluminescence. Abstract : We introduce here a new subclass of copper(i ) hybrid emitters simultaneously containing [Cu x I y ] z − anions and Cu + cations, separated in space by a Janus head ligand. When UV-irradiated at 298 K, these unique "Two-In-One" hybrids exhibit a short-lived green TADF with near-unity quantum yield and a strong solvatochromic effect. Moreover, they manifest a strong radioluminescence upon X-ray irradiation. These findings open up new possibilities for the design of highly performing TADF materials.